Possibilities of biological therapy application in intestinal inflammatory diseases against the background of pregnancy - O. V. Gaus; V. A. Ahmedov; T. S. Zhabrova (Лечащий Врач, 2021)
Number of studies related to safety of biological therapy in women patients with intestinal inflammatory diseases during pregnancy is increasing, but the issue is still unsolved due to ethical difficulty of their conducting. The paper systematizes available modern data on possibility of biological drug application in inflammatory intestinal diseases in the pregnant, the level of risk of their potential effect on the fetus was assessed.